Dampak Keterbatasan Sarana Prasarana dan Kompetensi Guru terhadap Kualitas Pembelajaran Penjas: Studi Kasus SD Sumedang - Susilawati, Diana; Mariam, Anisa Siti Nur; Nugraha, Adithya Warman; Rahman, Aam Ali (MAN Insan Cendekia Jambi, 2025)
This study aims to analyze how inadequate facilities and teachers’ professional competence affect the quality of Physical Education learning in elementary schools. This research employed a qualitative approach with a case study design involving the principal, Physical Education teachers, and students through structured interviews and direct observation. The findings reveal that insufficient facilities, such as damaged sports equipment and limited supporting infrastructure, serve as major obstacles in implementing effective learning. Furthermore, teachers’ professional competence, categorized as adequate, affects the variety of teaching methods, classroom management, and instructional innovation. Data analysis indicates that teacher creativity in modifying simple equipment becomes an adaptive strategy that helps maintain learning continuity, although it cannot fully overcome existing challenges. The discussion highlights that learning quality is influenced by the combination of both factors, where adequate facilities and optimal teacher competence are essential to achieving learning objectives. The study concludes that improving educational facilities and strengthening teacher competence are crucial for enhancing the overall quality of Physical Education learning.